Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Cerita Fungsi Permintaan Dan Penawaran Kelas Xi Ak Pm Smk Muhammadiyah 2 Surakarta Tahun Ajaran 2016/2017 - Fadhilah, Nurul; Rita P, Rita P Khotimah, S.Si., M.Sc (2017)
The purpose of research to describe the studentsdifficulties in completing the story about the function of demand and supply of class XI an analyze its causes. This research is descriptive qualitative. Subject research is students XI AK PM vacatinal high school Muhammadiyah 2 surakarta academic year 2016/2017. Data collection methods used in this study is a test, interviews, and documentation. Data analysis technique by reducing the data, the presentation of the data, and withdrawal conclusion. The results showed that the difficulties experienced by students in solving a function of demand and supply story: (1) difficulty understanding the questions on the metters, (2) difficulties in determining the formula function of demand and supply, and )difficulties in negative numbers arithmetic operations. Factor that cause students to experience difficulties that students don't understand the basic concept of demand and supply function, students still confution in understanding the language of mathematics, students have not mastered the material prerequisites such as linear equations, students don't understand the use of the formula function of demand and supply, erred in reading thesymbols on the function of demand and supply, students are less scrupulous in solving function of demand and supply.